Social capital in the tradition of eating bedulang in the people of Cerucuk Village, Badau District, Belitung Regency - Wulandah, Safirah; Iqbal, Muhamad; Yulianti, Iing (Harmoni Sosial: Jurnal Pendidikan IPS, 2021)
Indonesia has a variety of cultures that attract tourists because each has its uniqueness. Currently, cultural preservation is carried out to preserve and maintain Indonesian culture because every culture or tradition has social capital that can influence the community's social capital to achieve common goals. One culture or tradition with social capital is the tradition of eating bedulang, a tradition in the Belitung Regency. This study aims to determine the social capital in the tradition of eating bedulang in the Cerucuk Village community, Badau District, Belitung Regency. The approach used is a qualitative approach with a case study method. Data collection techniques using observation, interviews, and documentation studies. The findings of this study include the following: First, there is a traditional consultation in cooperation in preparing the implementation of the tradition of eating Bedulang; Second, there is a reciprocal relationship between expectations and what is felt by the community after following the tradition of eating bedulang so that it creates mutual trust between people; Third, there are values and norms in the tradition of eating bedulang, namely ethical values, aesthetic values, religious values, and social values as well as religious norms, decency norms, decency norms, and legal norms; Fourth, the impact of social capital contained in the tradition of eating bedulang is very influential by providing good benefits for people's lives in achieving common goals.